Two new species of Ooencyrtus (Hymenoptera, Encyrtidae), egg parasitoids of the bagrada bug Bagrada hilaris (Hemiptera, Pentatomidae), with taxonomic notes on Ooencyrtus telenomicida - Serguei V. Triapitsyn; Sharon A. Andreason; Nancy Power; Fatemeh Ganjisaffar; Lucian Fusu; Chrysalyn Dominguez; Thomas M. Perring (Journal of Hymenoptera Research, 2020)
In support of a biological control program in California, USA, against the bagrada bug, Bagrada hilaris (Burmeister) (Hemiptera, Pentatomidae), an invasive pest of Asian origin, colonies of two species of Ooencyrtus Ashmead (Hymenoptera, Encyrtidae) are maintained using B. hilaris eggs as host. One of them, Ooencyrtus mirus Triapitsyn & Power, sp. nov., is of Pakistani origin. It displays natural preference for bagrada bug eggs and is being evaluated in quarantine as a candidate for classical biological control. The other, Ooencyrtus lucidus Triapitsyn & Ganjisaffar, sp. nov., appears to be native to California, and we believe it switched to B. hilaris from native pentatomid hosts. Both new species are described and illustrated, as is the Old World species Ooencyrtus telenomicida (Vassiliev), for which a neotype is designated. The presented morphometric evidence as well as mitochondrial and nuclear ribosomal DNA sequence data separate Ooencyrtus mirus from O. telenomicida. A lectotype is designated for Ooencyrtus californicus Girault from California, which is morphologically similar to O. lucidus.